Desain User Interface Aplikasi Registrasi Pelanggan Pt. Icon(+) Palembang Berbasis Mobile - apriansyah (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
This Research aims to design a Customer Registration Application for PT. Indonesia Comnet Plus SBU Palembang as a place for customers to register, upgrade installation and make it easier for admins to manage data. Therefore, the authors designed a mobile-based application design that can be used flexibly. This application is designed to use the UML (Unified Modeling Language) language to describe the system designed and make it easier to visualize the system designed by the author using a web-based application, namely Figma to design the user interface of the application. This application was developed using the waterfall method where this method provides an ordered and systematic picture. This application design is expected to help PT. Indonesia Comnet Plus SBU Palembang in supporting customer needs in accordance with its functions and objectives. Keywords: Design, Mobile, Registrastion, PT. Indonesia Comnet Plus